PENINGKATAN LITERASI ANAK DI DESA SIMATORKIS MENGGUNAKAN STRATEGI BELAJAR TERBIMBING KEGIATAN KKN DALAM MEWUJUDKAN GENERASI CERDAS - Lili Herawati Parapat; Khairunnisah Khairunnisah; Rini Agustini; Saadah Mardiyah Pgb; Rawani Indah Tanjung; Maya Ritonga (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study aims to improve children's literacy in Simatorkis Village through the implementation of guided learning strategies in the 2025 Community Service Program (KKN). The research method used was a descriptive qualitative approach supported by simple quantitative data. The study was conducted from October to December 2025. The subjects consisted of 20 elementary school-aged children who participated in the four-week learning assistance program. Data collection techniques included observation, interviews, and documentation. The results showed an increase in children's literacy skills, including reading fluency, reading comprehension, and simple writing skills. The children's average literacy scores increased significantly after the implementation of the guided learning strategy. This strategy is effective because it provides gradual support, creates an interactive learning environment, and increases children's motivation and self-confidence. Therefore, guided learning strategies in KKN activities can be an alternative solution to improving children's literacy in rural areas and supporting the creation of an intelligent generation by 2025.